2008
DOI: 10.1002/arch.20277
|View full text |Cite
|
Sign up to set email alerts
|

Midgut mitochondrial transhydrogenase in wandering stage larvae of the tobacco hornworm, Manduca sexta

Abstract: Midgut mitochondria from fifth larval instar Manduca sexta exhibited a transhydrogenase that catalyzes the following reversible reaction: NADPH + NAD(+) <--> NADP(+) + NADH. The NADPH-forming transhydrogenation occurred as a nonenergy- and energy-linked activity. Energy for the latter was derived from the electron transport-dependent utilization of NADH or succinate, or from Mg++-dependent ATP hydrolysis by ATPase. The NADH-forming and all of the NADPH-forming reactions appeared optimal at pH 7.5, were stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…As reported in Vandock et al (2008), isolated midgut mitochondria from M. sexta catalyzed an NADPH-NAD + transhydro-genation as measured by AcPyAD reduction (Table 1). This NADH-forming reaction was the most active transhydrogenation observed.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…As reported in Vandock et al (2008), isolated midgut mitochondria from M. sexta catalyzed an NADPH-NAD + transhydro-genation as measured by AcPyAD reduction (Table 1). This NADH-forming reaction was the most active transhydrogenation observed.…”
Section: Resultssupporting
confidence: 53%
“…Spectrophotometric assessments of transhydrogenase were performed essentially as described by Fioravanti et al (1992) and Vandock et al (2008). Activities were measured by following acetylpyridine-NAD(P) (AcPyAD(P)) reduction at 375 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Indeed, careful experimentation has shown that fatbody and midgut tissues display increased levels Agarose gel of pCr products of M. sexta transhydrogenase fragment using degenerate primers. notes: Degenereate primers (5′ TAYCAYCANGTNTGGGGN3′ and 5′ rAACATrTCNArCATNCK3) designed against the conserved polypeptide sequences YhTVWG and rMLDMFK (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The developmental significance of these transhydrogenations and the role(s) they may play in postembryonic development was evaluated. 8 This transhydrogenase appears to be physiologically linked to the developmentally necessary NADPH-requiring mitochondrial E20-M.…”
Section: Introductionmentioning
confidence: 99%